Development of the popular scientific book of Nepenthes diversity in Tanta District forest areas, Tabalong Regency: Validity and Practicality - Riya Irianti; Mahrudin Mahrudin (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Developing teaching materials based on local potential is necessary for introducing objects in the surrounding environment to support student learning. This is expected to broaden the insights and knowledge of students so that they become more familiar with and know the object of the material being taught. Wetlands are the dominant area in the South Kalimantan region and can be one of the learning resources in producing a product that can support learning at all levels of education; this can be in the form of local potential-based teaching materials, one of which is a popular scientific book. This study aims to describe the validity and practicality of popular scientific books based on the results of research on the Diversity of Semar Pockets (Nepenthes) Forest Areas in Tanta District, Tabalong Regency ". The validity and practicality tests were carried out at the Preliminary field testing stage used in the Borg and Gall model development research at the validity test stage involving two validators, while the practicality test involved 30 students who had passed the Phanerogamae course. The results showed that the Popular Scientific Book "Diversity of Semar Bag Species (Nepenthes) in the Forest Area of Tanta District, Tabalong Regency," obtained a very valid and very practical category. The results of this study indicate that the popular scientific book prepared can be used further to test its effectiveness on the learning process and outcomes.Abstrak. Pengembangan bahan ajar yang berbasis potensi lokal sangat perlu dalam memperkenalkan objek yang ada di lingkungan sekitar dalam menunjang pembelajaran peserta didik. Hal ini diharapkan memperluas wawasan dan pengetahuan peserta didik lebih mengenal dan mengetahui akan objek materi yang dibelajarkan. Lahan basah merupakan kawasan yang dominan di wilayah Kalimantan Selatan, dapat menjadi salah satu sumber belajar dalam menghasilkan suatu produk yang dapat mendukung pembelajaran di semua tingkat pendidikan, hal ini dapat berupa bahan ajar berbasis potensi lokal salah satunya yaitu buku ilmiah populer. Penelitian ini bertujuan untuk mendeskripsikan kevalidan dan kepraktisan buku ilmiah popular berbasis hasil penelitian Keragaman Kantong Semar (Nepenthes) Kawasan Hutan di Kecamatan Tanta Kabupaten Tabalong”. Uji kevalidan dan kepraktisan dilaksanakan pada tahap Preliminary field testing yang digunakan dalam penelitian pengembangan model Borg and Gall pada tahap uji kevalidan melibatkan dua validator, sedangkan uji kepraktisan melibatkan 30 mahasiswa yang sudah lulus mata kuliah Phanerogamae. Hasil penelitian menunjukan Buku Ilmiah Populer ”Keanekaragaman Jenis Kantong Semar (Nepenthes) di Kawasan Hutan Kecamatan Tanta Kabupaten Tabalong” yang dikembangkan memperoleh kategori sangat valid dan sangat praktis. Hasil penelitian tersebut menunjukkan bahwa buku ilmiah popular yang disusun dapat digunakan lebih lanjut untuk uji efektivitasnya terhadap proses maupun hasil belajar.